2014
DOI: 10.1093/aje/kwu071
|View full text |Cite
|
Sign up to set email alerts
|

Dogaru et al. Respond to "Does Breastfeeding Protect Against 'Asthma'?"

Abstract: We thank Michael Kramer for his insightful comments (1) on our systematic review and meta-analysis on breastfeeding and childhood asthma (2). Following a concise summary of our findings, he points out the high heterogeneity of the results and addresses issues that might explain this, namely the phenotypic variability of asthma, lack of objective measurements, variable degrees of measurement bias, and residual confounding.We entirely agree with Professor Kramer that "asthma" is a label applied to a heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Interestingly, a meta-analysis of 12 human studies showed that the protective effect in most studies correlated with the (high) concentrations of transforming growth factor (TGF)-β1 or TGF-β2 in the milk (Oddy and Rosales 2010 ). A recent meta-analysis of studies published between 1983 and 2012 on breastfeeding and asthma in children reported a strong protective association at ages 0–2 years between breastfeeding and asthma, which diminished over time (Dogaru et al 2014a , b ). The availability of nutrients, and especially of milk oligosaccharides, in the intestinal tract of newborns also has a profound influence on the microbial species that are able to survive there.…”
Section: Dietary Exposure and Host Immunity In Early Lifementioning
confidence: 99%
“…Interestingly, a meta-analysis of 12 human studies showed that the protective effect in most studies correlated with the (high) concentrations of transforming growth factor (TGF)-β1 or TGF-β2 in the milk (Oddy and Rosales 2010 ). A recent meta-analysis of studies published between 1983 and 2012 on breastfeeding and asthma in children reported a strong protective association at ages 0–2 years between breastfeeding and asthma, which diminished over time (Dogaru et al 2014a , b ). The availability of nutrients, and especially of milk oligosaccharides, in the intestinal tract of newborns also has a profound influence on the microbial species that are able to survive there.…”
Section: Dietary Exposure and Host Immunity In Early Lifementioning
confidence: 99%
“…45 In the context of asthma, a recent systematic review and meta-analysis has shown a positive association of breastfeeding with reduced asthma/wheezing; however, after stratification by age, the protective association found at ages 0-2 years diminished over time. 46 Consistent with this, a study from Denmark showed that exclusive breastfeeding does not affect asthma and other allergic diseases by 7 years of age. 43 In summary, based on the many benefits for the mother and child, rather than allergy protective effects specifically, breastfeeding should be strongly encouraged for at least 6 months and should be continued while introducing solids into the diet (Table 1).…”
Section: The Role Of Breastfeeding In Prevention Of Allergic Diseasesmentioning
confidence: 57%
“…One recent prospective birth cohort study did interestingly show that continued breastfeeding while solids are introduced is associated with fewer food allergies . In the context of asthma, a recent systematic review and meta‐analysis has shown a positive association of breastfeeding with reduced asthma/wheezing; however, after stratification by age, the protective association found at ages 0–2 years diminished over time . Consistent with this, a study from Denmark showed that exclusive breastfeeding does not affect asthma and other allergic diseases by 7 years of age …”
Section: Post‐natal Immunomodulatory Dietary Strategies For the Primamentioning
confidence: 82%
“…The role of maternal atopy was not assessed (6). Two earlier meta-analyses reported similar results for young children, but also reported stronger associations among those with a maternal history of atopy (4,7).…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 99%
“…Two earlier meta-analyses reported similar results for young children, but also reported stronger associations among those with a maternal history of atopy (4,7). The authors of the recent meta-analysis concluded that additional work should to be done to analyze potential confounders and mediators such as daycare attendance and early respiratory illness, and to explore potential difference by ethnicity in the relationship of breastfeeding and childhood asthma (6,8,9). …”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 99%